CORPORATE GOVERNANCE DAN KARAKTERISTIK PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN - Muhammad Asril Arilaha (Jurnal Keuangan dan Perbankan, 2009)
The objective of this study was to give empirical evidence, the infl uence of corporategovernance, profi tability, and fi rm growth to dividend policy. Population of study was fi rms whichwere followed survey by The Indonesian Institute for Corporate Governance (IICG) in 2006-2008. Datawas collected by purposive sampling and multiple regression. The result showed there is no supportsubstitution that fi rm which had bad corporate governance mechanism would give dividend to investors.Firm profi tability and fi rm size gave positive infl uence to dividend policy, but fi rm growth gavenegative infl uence to dividend policy.